THE NEED TO INCREASE THE POTENTIAL OF THE REPUBLIC'S PROVINCES AND DISTRICT FINANCIAL RESOURCES DURING THE CORONAVIRUS PANDEMIC - P.Sh, Usmanov (Journal of Contemporary Business Law & Technology: Cyber Law, Blockchain, and Legal Innovations, 2024)
This article describes the financial potential of enterprises, the financial aspects of its organization, as well as the features of effective management of local finances, the need to attract financial resources to solve economic and financial problems that are becoming acute in practice.